Fostering Cultural Awareness through Gastronomy in UNSOED Student - Safrina Arifiani Felayati; Chendy Arieshanty Paramytha Sulistyo; Eka Yunita Liambo; Riefki Fajar Ganda Wiguna (SPHOTA: Jurnal Linguistik dan Sastra, 2025)
This study analyses the effectiveness of gastronomy in fostering cultural awareness among UNSOED students, emphasizing how food can serve as a bridge to cultural understanding. This study was conducted in five different classes with a total of 150 students from Fakultas Ilmu Budaya and Fakultas Ilmu Sosial dan Politik UNSOED. This study uses a qualitative experiential approach with a focus on interactive and practical learning. Students participate in gastronomy practices where they bring traditional foods from local and international cultures (e.g., mendoan, sandwiches, and baguettes), followed by tasting and discussion sessions. Data were collected through observation and reflective feedback from students to assess the impact of gastronomy experiences on the development of cultural awareness. This study found that tasting various foods significantly increased students' understanding of various cultural values and practices. In addition, this approach is in line with the objectives of the MBKM program, which emphasizes flexibility and real-world learning experiences. Gastronomy, as demonstrated in this study, has proven to be a practical and effective tool in fostering cultural awareness in students. By connecting food traditions to cultural history and social practices, students not only learn about different cultures but also develop a deeper appreciation for cultural diversity. The findings indicate that direct engagement with gastronomy significantly enhances students’ cultural awareness by providing an immersive learning experience. The study reveals that experiential learning through gastronomy fosters open-mindedness, appreciation for diversity, and critical thinking regarding cultural differences. This research contributes to the field of cultural education by demonstrating the effectiveness of gastronomy as an educational tool. It highlights the potential integration of culinary-based cultural education into university curricula, providing a model that can be adapted in other educational institutions